2005
DOI: 10.1007/s11882-005-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitous airborne fungi in chronic rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a confusing disease for both allergists and otorhinolaryngologists, partially due to its poorly understood pathophysiology and partially due to its limited treatment options. Several recent reports now provide evidence for a better understanding of the etiology and the relationship of CRS to airborne fungi, especially to Alternaria. First, the development of novel methods enables detection of certain fungi in mucus from the nasal and paranasal sinus cavities. Second, a non-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
(31 reference statements)
0
40
0
Order By: Relevance
“…18 Although it is accepted that, in allergic fungal rhinosinusitis, colonizing fungi are a central mechanism that drive disease, what has been controversial is whether there is a role for endogenous fungi in all cases of CRS. Support for this concept is based on the observation that fungi are universally present in the sinus cavity, 29 with the suggestion that CRS could develop in subjects in whom the usual state of immune nonresponsiveness breaks down, which allows a Th2 response to develop. These investigators demonstrated that subjects with eosinophilic CRS (and not the healthy controls) had circulating T-effector lymphocytes in response to Alternaria-secreted IL-5.…”
Section: Figure 2 Proliferation Of Naive T Cells Stimulated With Itrmentioning
confidence: 99%
“…18 Although it is accepted that, in allergic fungal rhinosinusitis, colonizing fungi are a central mechanism that drive disease, what has been controversial is whether there is a role for endogenous fungi in all cases of CRS. Support for this concept is based on the observation that fungi are universally present in the sinus cavity, 29 with the suggestion that CRS could develop in subjects in whom the usual state of immune nonresponsiveness breaks down, which allows a Th2 response to develop. These investigators demonstrated that subjects with eosinophilic CRS (and not the healthy controls) had circulating T-effector lymphocytes in response to Alternaria-secreted IL-5.…”
Section: Figure 2 Proliferation Of Naive T Cells Stimulated With Itrmentioning
confidence: 99%
“…Consequently, Staphylococcus aureus superantigens may have a role in the onset and severity of allergic diseases, namely asthma and allergic rhinitis. Not only bacteria, but also fungi, especially Alternaria, may play a role in the generation of chronic rhinosinusitis (41). Cytokines produced by tissuebound lymphocytes recruit eosinophils, which attack fungi, recognized as strangers by the immune system of patients with chronic rhinosinusitis.…”
Section: Immunologic Levelmentioning
confidence: 99%
“…Hence, there might be a comorbid IgE-mediated hypersensitivity to molds, but eosinophilic inflammation seems to be driven by a non-IgE-mediated mechanism. Besides, Alternaria is able to induce eosinophil degranulation (41). Therefore, innate eosinophilic response to certain environmental fungi may be important in the onset of inflammatory airways diseases, such as asthma and chronic rhinosinusitis.…”
Section: Immunologic Levelmentioning
confidence: 99%
“…Hellings et al [21] recently demonstrated that nasal application of S. aureus enterotoxin B is capable of aggravating experimental allergic rhinitis and asthma, with an increase in bronchial and systemic T-helper type 2 cytokine levels [21]. Besides bacterial enterotoxins, Ponikau et al [28] reported on the potentially important role of fungi, especially Alternaria, in the generation of NP. By their capacity to induce eosinophil degranulation, Alternaria may contribute to the inflammatory spectrum of CRS with/without NP.…”
Section: Nasal Polyp Disease and Asthmamentioning
confidence: 99%